EARLY DIAGNOSIS OF KIDNEY PATHOLOGY BY CYSTATIN C MARKER IN GLYCEROL-INDUCED ACUTE KIDNEY INJURY MODEL RATS - Ma’mura I. Jabborova; Bakhtiyor U. Iriskulov (Central Asian Journal of Medicine, 2024)
Acute Kidney Injury (AKI) is a rapid deterioration of kidney function, presenting significant health risks if not promptly diagnosed and managed. Traditional biomarkers like serum creatinine and blood urea nitrogen (BUN) often fail in early detection. This article evaluates Cystatin C, a cysteine protease inhibitor, as a potential early biomarker for AKI using a glycerol-induced AKI model in rats. Findings indicate that Cystatin C levels rise sooner than traditional markers, highlighting its efficacy in early diagnosis and the potential for better clinical outcomes through timely intervention. Purpose: To study the diagnostic and prognostic significance of cystatin C in the early diagnosis of acute kidney injury caused by chemical poisoning. Materials and methods: experiments were conducted on 45 white Wistar rats weighing 180-220 g. Experimental acute kidney injury was induced by a single injection of 10 ml/kg 50% glycerol solution into the hind leg muscles of model rats. In the first 24 hours, the dynamics of blood cystatin C, creatinine, urea, residual nitrogen, total proteins in blood, albumin, globulin, acid-base balance, blood electrolytic indicators (Na, K, Ca,P,Mg) were studied in experimental model rats. Results: at all stages of the experiment, it was observed that the amount of Cystatin C increased, while the amount of creatinine did not change. Conclusion: Cystatin C is one of the optimal biomarkers for early diagnosis of acute kidney diseases.